North American sociology of religion: Critique and prospects - Williams, Rhys H. (Critical research on religion, 2013)
We assess the current state of sociology of religion, particularly in the United States, for the extent to which a “critical sociology of religion” currently exists and how it might look if it did. We focus particular attention on two areas of inquiry: religion and health; and religion and violence.